Advances in bio food packaging – An overview. Issue 9 (September 2021) - Yuvaraj, D.; Iyyappan, J.; Gnanasekaran, R.; Ishwarya, G.; Harshini, R.P.; Dhithya, V.; Chandran, M.; Kanishka, V.; Gomathi, K.
Abstract: In recent years, there has been an increase in demand for bioactive techniques in the food packaging industry. Although edible packaging is popular, it has yet to be effectively implemented into the market. Packaging made of plastics and chemicals is widely employed in the market today, posing a threat to the environment and living creatures. This research attempts to show current breakthroughs and progress in the field of biodegradable packaging. When compared to ancient packaging materials, bio-based packaging materials are safer. Sustainable biodegradable packaging materials can be made from edible films, coatings, and other bio food packaging techniques made from various biological resources. This paper discusses the important qualities and advantages of several bio-based packing materials. It is highlighted the advantages of bio-based packaging materials over synthetic packaging materials. It has been debated the importance of employing bio-based packaging to mitigate the environmental risks associated with traditional packaging technologies. Many researchers may be prompted by this study to focus on packaging reformulation options. Thus, we can attain food packing materials by considering customer's economic and sustainability aspects. Abstract : Sustainable development; bioactive strategies; biopolymers; edible films; environmental pollution